L’ordine pubblico internazionale e la Costituzione. Prime note (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay analyzes the transformations of the so called international public order, as it is applied by Italian tribunals in matters relating to artificial human fertilization. It recalls the constitutional sentence that forty years ago established the supremacy of constitutional ethic upon the catholic Church’s ethic, notwithstanding the special protection that the Constitution itself affords to it.
Keywords: Artificial human fertilization; international public order; constitutional values; women’s fundamental rights; children’s fundamental rights